Rediscovery and redescription of Callicarpa chazaliei Versluys, 1899 (Cnidaria: Hydrozoa) in the southwestern Atlantic Ocean - de Moura, Andreza Campos; Campos, Felipe Ferreira; Pérez, Carlos Daniel (Zootaxa, 2022)
The genus Callicarpa Fewkes, 1881 presently comprises two species of Leptothecate hydroids. Herein we redescribe one of these, C. chazaliei Versluys, 1899, originally described from Florida and known elsewhere only from Venezuela. With the only morphological account of this species being that of the original description, a detailed redescription and illustrations of it are provided. Specimens were collected in the Potiguar Basin off the coast of Rio Grande do Norte, Brazil, at a depth of 65 m, during a project focusing on the characterization and monitoring of an oil extraction basin.